Antimicrobial study of Rasakarpura Drava and Rasakarpura Gel - Neky J Mehta, Dr (International Journal of Pharmaceutical & Biological Archive, 2014)
Antimicrobial study of Rasakarpura Drava and Rasakarpura Gel